Tragic End or Expected Destiny?: Pulmonary Edema Due to Sewing Ring Dehiscence of Bioprosthetic Mitral Valve - Ghalyoun, Bader Abu (JACC Case Rep, 2019)
The present case is unique because it describes transcatheter mitral valve replacement with a valve-in-valve procedure in an emergent setting of pulmonary edema and cardiogenic shock. Although transcatheter mitral valve replacement is in its initial phase, it remains a viable option in an emergency. Further research is needed to evaluate the short term and long-term outcomes. (Level of Difficulty: Beginner.)